Equalizing Discrimination and Cartel Pricing in Transport Rate Regulation - Boyer, Kenneth D. (Journal of Political Economy, 1981)
There are two possible outcomes of transport regulation: (1) maintaining a carrier cartel and (2) imposing equalizing discrimination against advantaged and in favor of disadvantaged shippers. Both functions have required a complex rate structure to enforce the respective forms of price discrimination. Using a sample of freight bills from motor carriers and railroads, this paper demonstrates that the principal result of motor carrier regulation has been to maintain a cartel of truckers, while railroad regulation has thwarted the wishes of the railroad cartel by imposing equalizing discrimination on weak and strong shippers. Motor carrier rates respond in an economically rational manner to costs and shipper bargaining power; rail rates are either unresponsive or perversely responsive to the same factors. Deregulation should have divergent effects in the two industries.